Socio-Economic Benefits of Biogas for Women in Household Cooking In Nepal - Pokhrel, Rajendra Kumar; Pokhrel, Anju (Tribhuvan University Journal, 2023)
The bio-gas is viable technology as household cooking solution to reduce smoke related diseases, accidents of burning, good source of organic fertilizer, save time for collection of fuel wood and change the kitchen environment. It is important energy source. Women empowerment is possible through bio-gas in Nepalese kitchens and promotes changes in cooking practice. The bio-gas programme is most effective and successful programme in rural Nepal. By studying and understanding the potential of biogas, the research can provide valuable insights into the potential of biogas to improve the lives of semi-urban communities and contribute to sustainable development with a specific focus on women’ welfare. The researcher collected primary data and information through survey questionnaire and secondary data were gathered from relevant reports and documents published by government and bio-gas companies. The study employed both quantitative as well as qualitative techniques of data analysis. For the study, the respondents were broadly categorized in two distinct categories: households with privately owned biogas plants and the households connected to commercial biogas plant recently launched in Ghorahi Sub-Metropolitan City. For quantitative data, questionnaire was distributed among 60 randomly selected households having privately owned biogas plant, and 40 respondents were also randomly selected from among the 50 households connected to commercial biogas plant. Finally, qualitative findings from key informant interview (KII) and observation were also applied to justify and strengthen the quantitative findings. For this purpose, interviews were conducted among the Mayor of Ghorahi Sub-Metropolitan City, DE and Ward Chairman of project site. Major proportion of waste in Ghorahi is biomass that includes kitchen waste, farm residue and livestock dung that has been utilized to produce flammable methane gas. Bio-gas is cost effective, so, households of all income groups can afford the technology. Bio-gas as clean fuel enhances Nepalese women’s culinary practice, plays crucial role in women’s welfare; which is the first step towards women empowerment. The study has shown that women and girls have greatly relieved from the drudgery of fuel wood collection and smoke related diseases.